MINUMAN SERBUK INSTAN DARI KULIT BUAH NAGA DENGAN FORMULASI ASAM DAN BASA YANG BERBEDA: Instant Powder Drink from Dragon Fruit Peel with Different Formulation of Acid and Base - Lasmini Yati; Arinda Dwi Safitri; Deni Aji Saputra; Iffah Muflihati; Sari Suhendriani (Agroindustrial Technology Journal, 2022)
Dragon fruit peel is one of the wastes that has not been widely used. Instant powder drink is one of the products of choice because it is more practical to consume. The utilization of dragon fruit peel waste into instant powder drinks can be an innovation in food processing. This study aims to determine the effect of differences in the amount of citric acid and sodium bicarbonate on the characteristics of dragon instant powder drink from dragon fruit peel. The experimental design used was a completely randomized design with a comparison of acid (citric acid) and base (sodium bicarbonate) treatment. The results showed that the use of acids and bases did not affect the water content and the panelists' preference for the product. The lower the amount of acid will decrease the dissolution time and increase the solubility percentage. The difference in the amount of citric acid and sodium bicarbonate affects the intensity of the sour taste produced but has no effect on other sensory properties.